The Implementation of the honest opportunity probation with enforcement demonstration field experiment: experiences from the field - Zajac, Gary (Journal of crime and justice, 2021)
The Honest Opportunity Probation with Enforcement Demonstration Field Experiment (HOPE DFE) was the largest and most rigorous test of the HOPE model. Outcomes from this experiment indicated null or even iatrogenic results for HOPE, in spite of high implementation fidelity. This article explores in greater detail the implementation experience at the four DFE sites, examining factors that may elucidate these outcomes. The implementation experience was smooth, although HOPE at one site clashed with the existing organizational culture. The implementation of HOPE did seem to be resilient to local administrative variations and the site that struggled to accept HOPE yielded a successful implementation. Still, good implementation experiences did not produce positive outcomes, suggesting that HOPE was an ineffective model that was implemented well. While the HOPE teams overall were enthusiastic about HOPE, thinking that HOPE was the way that probation should be, this faith in the model did not translate into measurable outcomes, suggesting that correctional policy should be driven by evidence rather than aspirations.